2022
DOI: 10.1590/s0004-2803.202203000-72
|View full text |Cite
|
Sign up to set email alerts
|

IS HOMEOSTASIS MODEL ASSESSMENT FOR INSULIN RESISTANCE >2.5 A DISTINGUISHED CRITERIA FOR METABOLIC DYSFUNCTION-ASSOCIATED FATTY LIVER DISEASE IDENTIFICATION?

Abstract: Background Insulin resistance (IR), assessed by different criteria, is an important factor in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). More recently with the characterization of this metabolic dysfunction-associated fatty liver disease (MAFLD), one of the proposed criteria for this diagnosis has been the determination of the homeostasis model assessment-insulin resistance (HOMA-IR). Objective: The purpose of this study was to evaluate the relationship of HOMA-IR>2.5 with clinical, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Interestingly, none of them dealt with viral hepatitis. Instead, in this issue of Archives of Gastroenterology, Barreto et al (14) evaluated retrospectively Brazi lian subjects with NAFLD and found that HOMA IR values could identify subjects more prone to develop advanced fibrosis or cirrhosis. The authors suggested that HOMA IR could be a valuable tool to identify those patients with non-alcoholic steatohepatitis, but prospective validation and comparison of HOMA IR with other readily available non-invasive markers of fibrosis in the Brazilian population is still an unmet need.…”
mentioning
confidence: 99%
“…Interestingly, none of them dealt with viral hepatitis. Instead, in this issue of Archives of Gastroenterology, Barreto et al (14) evaluated retrospectively Brazi lian subjects with NAFLD and found that HOMA IR values could identify subjects more prone to develop advanced fibrosis or cirrhosis. The authors suggested that HOMA IR could be a valuable tool to identify those patients with non-alcoholic steatohepatitis, but prospective validation and comparison of HOMA IR with other readily available non-invasive markers of fibrosis in the Brazilian population is still an unmet need.…”
mentioning
confidence: 99%